Islamic Empowerment of Red Brick Craftsmen: Enhancing Welfare in Julukanaya Village, Gowa Regency - Suarni, Agusdiwana; Rahmah, Syahidah; Nurhana, Nurhana (Jurnal Ekonomi Balance, 2024)
The aim of this research is to determine Islamic empowerment for red brick craftsmen in Julukanaya Village and to determine the impact of Islamic empowerment on improving the welfare of red brick craftsmen in Julukanaya Village. The type of research method used is descriptive qualitative which uses field research methods (primary data) and library research (secondary data). Primary data is data sourced from informants who know clearly and in detail about the problem being studied, namely red brick business owners and red brick craftsmen as well as community figures, while secondary data is obtained by researchers from books that are appropriate to the problem being studied. The results of the research show that the red brick business is managed together with business owners and red brick craftsmen so that it can improve the economic welfare of the people in Julukanaya Village so that they can meet their daily needs and can improve their children's education. Islamic empowerment of red brick craftsmen in Julukanaya Village, Gowa Regency is a collaboration or form of mutual help between business owners and red brick craftsmen, where the materials and land to be managed come from the business owner. The income level of the people in Julukanaya Village, especially red brick craftsmen, experienced an increase in prosperity because it had an impact on increasing the economy in the surrounding community